ANALISIS LAJU TIMBULAN, KOMPOSISI, DAN KARAKTERISTIK SAMPAH RUMAH TANGGA DI DESA ANGANTAKA - Sastra Wibawa, I Made; Satya Graha, I Made; Ari Yudiaskara, Dewa Ngakan (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2024)
Angantaka Village, covers an area of approximately 239 hectares with a population of around 4,376 people and 1,458 households. According to SNI 19-3983-1995, Angantaka Village is classified as a small town with a population of less than 100,000. Waste management system in the village largely follows the traditional method of collect, transport, and dispose without any sorting. The main issues contributing to the waste problem in Angantaka Village include a lack of community awareness regarding proper waste management and the absence of adequate temporary waste disposal facilities. Most of the waste from Badung Regency, including Angantaka Village, is transported to the Suwung landfill. Therefore, composition, and characteristics of household waste, which would help in estimating the land requirements and the costs for constructing and operating a 3R (Reduce, Reuse, Recycle) waste processing facility. The study revealed that the average domestic waste generation is 0.6 kg per person per day, with wet waste, including food scraps and garden waste, amounting to 1,519.78 kg per day, and dry waste, such as plastics, paper, and metals, totaling 1,360.55 kg per day. This data is crucial for designing a 3R-based Temporary Waste Management Facility in Angantaka Village.